2022
DOI: 10.1525/fsr.2022.34.2-3.155
|View full text |Cite
|
Sign up to set email alerts
|

Nordic Design

Abstract: Legal financial obligations serve a range of practical and ideological functions within the modern American criminal justice system. Criminal fines are punitive in nature and intended to reflect the severity of the offense as well as having a deterrent component. When assessed in conjunction with other financial penalties, including fees and restitution, the collective economic burden of these sanctions can be significant. An increasingly robust body of literature highlights the unequal impact and collateral h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The results of the current inquiry suggest that these assessments should not only take into account the instant or active case but also consider an individual's financial situation in light of all of the criminal justice debts that they must satisfy. Similarly, U.S. jurisdictions might consider the benefits of the European day fine model in which financial punishments are based on both the seriousness of the offense and the defendant's income at his or her “day job” (Colgan, 2017; Hillsman, 1990; Hyatt et al., 2022). Although very few American courts have implemented this model, existing evaluations show promising results, including increased perceptions that fines are applied fairly, in addition to an increase in court revenue (Turner & Petersilia, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current inquiry suggest that these assessments should not only take into account the instant or active case but also consider an individual's financial situation in light of all of the criminal justice debts that they must satisfy. Similarly, U.S. jurisdictions might consider the benefits of the European day fine model in which financial punishments are based on both the seriousness of the offense and the defendant's income at his or her “day job” (Colgan, 2017; Hillsman, 1990; Hyatt et al., 2022). Although very few American courts have implemented this model, existing evaluations show promising results, including increased perceptions that fines are applied fairly, in addition to an increase in court revenue (Turner & Petersilia, 1996).…”
Section: Discussionmentioning
confidence: 99%
“… For examples of research on LFOs outside of the United States, please see Hyatt et al. (2022), Kantorowicz‐Reznichenko and Faure (2021), Miethe and Lu (2005), Nagrecha (2020), and O’Malley (2009). …”
mentioning
confidence: 99%
“…In the latest fiscal cycle of the time period investigated, the city projected 23 percent of its funds to come from fines (U.S. Department of Justice, 2015, p. 10).5 For examples of research on LFOs outside of the United States, please seeHyatt et al (2022),Kantorowicz-Reznichenko and Faure (2021),Miethe and Lu (2005),Nagrecha (2020), andO'Malley (2009).6 Municipal courts typically handle low-level misdemeanor or traffic offenses versus superior courts whose jurisdiction covers felony offenses.7 See alsoRios (2019) for more on the "racial states of municipal governance. "8 In many states, offenders pay both restitution and compensation, the latter of which is assessed to all offenders, regardless of if there was a direct victim in that situation; see also,Katzenstein and Waller (2015) andMartin and Fowle (2020).9 Two recent works discuss this in greater depth:Harris et al (2019) provide two case studies that demonstrate how private entities, which run court-ordered programs and prison services, profit from LFOs;Katzenstein et al (2020) discuss "commissions/kickbacks" which funnel fees to private entities when incarcerated people, their families, or their friends pay for the use of a prison phone, commissary, or other services.10 SeeNeedham et al (2020) for an ethnographic account of the confusion faced by those assessed legal debt in fine-only misdemeanor cases.11 See alsoLink's review (2022) which presents some conflicting evidence on the relationship between LFO debt and increased recidivism rates, including a list of studies that found null effects or inverse relationships.…”
mentioning
confidence: 99%